Diagnostic and prognostic value of the Laboratory Risk Indicator for Necrotising Fasciitis (LRINEC) based on an 18 years' experience. (February 2023) - Breidung, David; Malsagova, Asja T.; Barth, Andrè A.; Megas, Ioannis-Fivos; Billner, Moritz; Hitzl, Wolfgang; Reichert, Bert
Summary: Background: Necrotising fasciitis (NF) represents a rare but often life-threatening condition. Early diagnosis and surgical treatment are of vital importance. The LRINEC score was developed to distinguish necrotising fasciitis from other soft tissue infections (STI) at initial evaluation using six laboratory values. In this retrospective study, we attempted to determine the diagnostic and prognostic value of the LRINEC score. Methods: A total of 125 patients, hospitalised in our clinic between 2003 and 2021 with a histologically confirmed diagnosis of necrotising fasciitis (NF group) and 319 patients with surgically treated soft tissue infections (STI group) were included in this study. Individual LRINEC scores were calculated and analysed retrospectively. Results: The sensitivity of the LRINEC score at the cut-off point of ≥ 6 was 59%, whereas the specificity was 82%. The positive and negative predictive values were 57% and 84%, respectively. The mean LRINEC score was significantly higher in the NF group than in the STI group (6.0 compared to 2.4, respectively). All clinical outcome parameters such as amputation and mortality rates (15% vs 1%) were found to be significantly higher in the NF group ( p <0.001). Within the NF group, there was no statistically significant association between the LRINEC score and clinical outcomes except for the necessary number of operations. Conclusion: In isolation, we found the LRINEC score not to be a reliable enough diagnostic tool for the differentiation between NF and other soft tissue infections, because of its low sensitivity. Although we cannot recommend it as a prognostic tool either, we do believe it can be a useful adjunct to the clinical suspicion of NF.